Verification of Dose Calculation Accuracy THERPLAN Treatment Planning System of 2D SAD treatment technique - Kaduga Altwieb; Farag Almasrub (African Journal of Advanced Pure and Applied Sciences, 2025)
This study evaluates the accuracy of the THERPLAN PLUSE version 1.2 Treatment Planning System (TPS) for dose calculation in 2D SAD setups, focusing on its performance across various treatment configurations. Measurements were conducted using a 6 MeV photon beam from an Elekta-Precise linear accelerator, employing a pre-calibrated FC65p ionization chamber and a Scanditronix water phantom. Dose comparisons were made between the TPS-calculated values and measured doses across a range of setups, including different SSDs, field sizes, wedge angles, asymmetric fields, parallel-opposed fields, and four-field box techniques. Results demonstrated strong concordance between calculated and measured doses, with deviations averaging 0.85% and remaining well within the International Commission on Radiation Units and Measurements (ICRU) tolerance of ±5%. Specific setups, such as wedge and asymmetric fields, showed deviations below ±1%, highlighting the robustness of THERPLAN in handling complex geometries. Comparisons with published benchmarks further validated the accuracy of the TPS in dose calculation. These findings underscore the reliability of THERPLAN TPS for routine clinical use in radiotherapy. The study emphasizes the importance of regular quality assurance and independent dose verification systems to ensure consistent treatment accuracy and patient safety.